Distinguishing post‐translational modifications in dominantly inherited frontotemporal dementias: FTLD‐TDP Type A (GRN) vs Type B (C9orf72). (28th July 2022) - Cracco, Laura; Doud, Emma H.; Hallinan, Grace I.; Garringer, Holly J.; Jacobsen, Max H.; Richardson, Rose M.; Buratti, Emanuele; Vidal, Ruben; Ghetti, Bernardino; Newell, Kathy L.
Abstract: Aims: Frontotemporal dementias are neuropathologically characterised by frontotemporal lobar degeneration (FTLD). Intraneuronal inclusions of transactive response DNA‐binding protein 43 kDa (TDP‐43) are the defining pathological hallmark of approximately half of the FTLD cases, being referred to as FTLD‐TDP. The classification of FTLD‐TDP into five subtypes (Type A to Type E) is based on pathologic phenotypes; however, the molecular determinants underpinning the phenotypic heterogeneity of FTLD‐TDP are not well known. It is currently undetermined whether TDP‐43 post‐translational modifications (PTMs) may be related to the phenotypic diversity of the FTLDs. Thus, the investigation of FTLD‐TDP Type A and Type B, associated with GRN and C9orf72 mutations, becomes essential. Methods: Immunohistochemistry was used to identify and map the intraneuronal inclusions. Sarkosyl‐insoluble TDP‐43 was extracted from brains of GRN and C9orf72 mutation carriers post‐mortem and studied by Western blot analysis, immuno‐electron microscopy and mass spectrometry. Results: Filaments of TDP‐43 were present in all FTLD‐TDP preparations. PTM profiling identified multiple phosphorylated, N‐terminal acetylated or otherwise modified residues, several of which have been identified for the first time as related to sarkosyl‐insoluble TDP‐43. Several PTMs were specific for either Type A or Type B, while others were identified in both types. Conclusions: The current results provide evidence that the intraneuronal inclusions in the two genetic diseases contain TDP‐43 filaments. The discovery of novel, potentially type‐specific TDP‐43 PTMs emphasises the need to determine the mechanisms leading to filament formation and PTMs, and the necessity of exploring the validity and occupancy of PTMs in a prognostic/diagnostic setting.